2009
DOI: 10.1186/1471-2369-10-13
|View full text |Cite
|
Sign up to set email alerts
|

A human glomerular SAGE transcriptome database

Abstract: BackgroundTo facilitate in the identification of gene products important in regulating renal glomerular structure and function, we have produced an annotated transcriptome database for normal human glomeruli using the SAGE approach.DescriptionThe database contains 22,907 unique SAGE tag sequences, with a total tag count of 48,905. For each SAGE tag, the ratio of its frequency in glomeruli relative to that in 115 non-glomerular tissues or cells, a measure of transcript enrichment in glomeruli, was calculated. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
0
21
0
Order By: Relevance
“…AL049313), representing the 3= end of the CLIC5 gene, was also enriched compared with nonglomerular ECs (52). Enrichment of the CLIC5 transcript in glomeruli, which is similar to that observed for transcripts of podocytespecific proteins (44), suggests that CLIC5 might play an important functional role in the glomerulus.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…AL049313), representing the 3= end of the CLIC5 gene, was also enriched compared with nonglomerular ECs (52). Enrichment of the CLIC5 transcript in glomeruli, which is similar to that observed for transcripts of podocytespecific proteins (44), suggests that CLIC5 might play an important functional role in the glomerulus.…”
mentioning
confidence: 67%
“…We have reported that the transcript for chloride intracellular channel 5 (CLIC5) is enriched ϳ800-fold in human glomeruli compared with pooled nonglomerular tissues and cells by serial analysis of gene expression (SAGE) (44). A similar enrichment of the CLIC5 transcript is also evident in a human glomerular SAGE library that was compared with libraries from microdissected nephron segments (13), and the CLIC5 transcript is enriched in a mouse glomerular expressed sequence tag library compared with whole kidney (27).…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…It is expressed throughout the cytoplasm and plasma membrane of the podocyte, but is not expressed by other human glomerular cell types (Figure 1). Gene expression analysis in human kidney supports an expression pattern limited to glomeruli, and in particular, podocytes (28)(29)(30). In contrast, this podocyterestricted pattern in humans is not found in mice (31) or rats (32), where PLA 2 R is expressed by glomerular cells other than podocytes.…”
Section: Antigen Identification In Human Diseasementioning
confidence: 97%
“…14,15 The kidney is a key organ for BP regulation and the site of highest FGF1 expression (http://www.proteinatlas.org/ ENSG00000113578/tissue). FGF1 is one of the glomerulusenriched genes [16][17][18][19] and previous immunochemistry confirmed the exclusive expression of FGF1 within apparently normal human glomeruli. 6,20 A number of mRNAs (i.e., Nephrosis 1, congenital, Finnish type [nephrin] gene, NPHS1; Nephrosis 2, idiopathic, steroid-resistant [podocin] gene, NPHS2) most tightly coexpressed with FGF1 in kidneys examined here are known as key structural constituents of the glomerulus.…”
Section: Discussionmentioning
confidence: 98%